2020
DOI: 10.1111/bjh.16997
|View full text |Cite
|
Sign up to set email alerts
|

Androgen derivatives improve blood counts and elongate telomere length in adult cryptic dyskeratosis congenita

Abstract: Dyskeratosis Congenita (DKC) is a systemic disorder caused by mutations resulting in impaired telomere maintenance. Clinical features include bone marrow failure and an increased risk of developing hematological malignancies. There are conflicting data whether androgen derivatives (AD) can elongate telomeres in vivo and whether AD treatment enhances the risk of gaining myelodysplastic syndrome-related mutations. Seven TERC or TERT-mutated DKC patients underwent AD treatment. All patients revealed hematological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 15 publications
2
25
0
Order By: Relevance
“…ADs are, e.g., able to activate the erythropoietin receptor in progenitor cells [29]. Of note, all effects including telomere elongation were observed in a relatively short time, in line with previous studies reporting clinically relevant response to AD treatment within the first three months in most cases [22,23].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…ADs are, e.g., able to activate the erythropoietin receptor in progenitor cells [29]. Of note, all effects including telomere elongation were observed in a relatively short time, in line with previous studies reporting clinically relevant response to AD treatment within the first three months in most cases [22,23].…”
Section: Discussionsupporting
confidence: 88%
“…Treatment with ADs is able to stimulate telomere elongation in patients with TERC or TERT mutations, as observed in our work [22] and in previous studies [18][19][20]. We therefore tested whether a relatively short treatment with ADs could cause an increase in telomere length in vitro in BM-MNCs.…”
Section: Danazol Oxymetholone and Nandrolone Cause Telomere Elongation Of Bm-mnc And The Improved Proliferation Is Abolished By The Additsupporting
confidence: 71%
See 1 more Smart Citation
“…Flow-FISH analysis of telomere length was carried out as previously described [27,28]. Briefly, vital frozen mononuclear cells from peripheral blood were mixed with a FITC labeled telomere specific (CCCTAA)3-peptide nucleic acid FISH probe (Eurogentec, Seraing, Belgium) for DNA-hybridization followed by DNA counterstaining with LDS 751 (Sigma, St. Louis, MO, USA).…”
Section: Fluorescence In Situ Hybridization (Flow-fish)mentioning
confidence: 99%
“…A recent study indicated that in leukocytes of COVID-19 patients telomere attrition below the 10 th percentile is more frequent than in healthy controls (Froidure et al, 2020), however the results of this study might be affected by the lymphopenia observed in COVID-19 patients (Benetos et al, 2020). To further investigate if this alternative biomarker for biological age is accelerated, we analyzed telomere length in lymphocytes of 19 COVID-19 patients with Flow-FISH, as described in detail before (Ferreira et al, 2020; Kirschner et al, 2020). In comparison to the telomere length distribution of 356 healthy controls (Werner et al, 2015) there was overall no evidence for significant telomere attrition in COVID-19 patients (Figure 2C,D).…”
Section: Introduction Results and Discussionmentioning
confidence: 99%